THE PROTECTION OF THE ACCUSED'S RIGHTS THROUGH THE INSTITUTION OF PETITIONS AND COMPLAINTS - Igilikov Jaksilik Joldasbaevich (Scholar Express Journals, 2025)
The article examines the institute of filing petitions and complaints in the criminal process of the Republic of Uzbekistan as an important legal mechanism for protecting the rights of defendants. The prosecutorial role of the accused, his rights and obligations, as well as the importance of filing petitions and complaints at the pre-trial stage are investigated. Particular attention is paid to the defender's role in the implementation of the accused's procedural rights and their influence on the course of the investigation. The possibility of the accused's active participation in the collection and verification of evidence, as well as in appealing against the decisions and actions of law enforcement agencies is considered. The use of these institutions to ensure legality, objectivity, and justice in criminal proceedings is analyzed.
Keywords: Criminal process; defendant rights; pre-trial stage; petition